1996
DOI: 10.1007/bf00399609
|View full text |Cite
|
Sign up to set email alerts
|

Stationary phase development of Trimmatostroma abietis

Abstract: Processes of anamorph cell replication in Trimmatostroma abietis are described. Growth and conidiation are delimited on the basis of morphological, ultrastructural and ecological criteria. Cellular expansion shifts from bidirectional intercalary in exponential phase cells to isodiametric in late stationary phase cells, in the latter case with endogenous asexual reproduction. Ultrastructural similarities to dothideaceous black yeasts are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The morphological plasticity of MCF is well-known and described for several species [42,49,50], and drastic morphological shifts following changes in microenvironmental conditions were observed, with meristematic hyphae appearing in response to temperature and desiccation stress [30,51]. A conversion from yeast-like to meristematic growth was also considered in the description of K. petricola, and the meristematic growth and penetration of torulose hyphae was associated to stone biodeterioration [32,52].…”
Section: Hyphal Morphologymentioning
confidence: 99%
“…The morphological plasticity of MCF is well-known and described for several species [42,49,50], and drastic morphological shifts following changes in microenvironmental conditions were observed, with meristematic hyphae appearing in response to temperature and desiccation stress [30,51]. A conversion from yeast-like to meristematic growth was also considered in the description of K. petricola, and the meristematic growth and penetration of torulose hyphae was associated to stone biodeterioration [32,52].…”
Section: Hyphal Morphologymentioning
confidence: 99%
“…A teleomorph is known only for Hyphospora, viz., Comminutispora agavaciencis Ramaley (Ramaley 1996). Endoconidia also occur in other black meristematic genera such as Alternaria (Tsuneda and Currah 2006), Aureobasidium (Hermanides-Nijhof 1977), Capnobotryella (Hambleton et al 2003;Tsuneda and Currah 2006), Coniosporium , Exophiala (Padhye et al 1996), Hormonema (Hermanides-Nijhof 1977), Knufia (Tsuneda and Currah 2004;Tsuneda et al 2005), Sarcinomyces (Wollenzien et al 1997), Scleroconidioma (Tsuneda et al 2000;Hambleton et al 2003), Trimmatostroma (Figueras et al 1996;Zalar et al 1999b), and Wangiella (Matsumoto et al 1990), but in these genera, endoconidia occur only sporadically and (or) are not the primary asexual reproductive propagules. These endoconidium-forming fungi are distributed among at least four orders in the Ascomycota; Chaetothyriales, Dothideales, Capnodiales, and Pleosporales Hambleton et al 2003;Tsuneda et al 2004a;Tsuneda and Currah 2006;Crous et al 2007a).…”
Section: Introductionmentioning
confidence: 97%
“…Members of the Dothideales enhance their stress-tolerance with increased melanization (Figueras et al, 1996) combined with thick cell walls and meristematic growth. Ultrastructural studies of the halophilic black yeasts Hortaea werneckii, Phaeotheca triangularis and Trimmatostroma salinum cell walls showed that the organisation of melanin granules is dependent on the concentration of salt in the medium (Kogej et al, 2001;.…”
Section: Discussionmentioning
confidence: 99%